RESEARCH ON THE DESIGN OF GUIDE PLATE FOR TANDEM HONEYCOMB STABILITY MAINTANCE - CHEN Dong; LU ZhaiJun; XIONG YuPu (Jixie qiangdu)
Based on the application of the honeycomb in the square guide rail,analyzed the tandem honeycomb deformation stability by experiments. Found tandem honeycomb is prone to instability in the impact process for the effect of uneven strength of simple honeycomb and impact load deflection. Analysis shows that the plate, with low intensity or its sectional dimension is smaller than guide rail section, is difficult to prevent honeycomb instability. To improve the effect of connection on keep tandem honeycomb deformation stability, studied the relationship among plate sectional dimension, guide rail sectional dimension and plate deflection degree from the theoretical level: when the guide rail sectional dimension unchanged, the longer the length of connection plate is, the smaller the deflection angle of plate is, the smaller the friction between plate and guide rail is, the better the guiding function of connection plate is. Based on the conclusion, designed a new guiding plate, it is not only improves tandem honeycomb deformation stability, but also solves the honeycomb peeling.